Pensionärsjävlar: revolt mot eller ett upprepande av negativa ålderskoder? (Sociologisk Forskning, 2013)
Old bastard – rebellion against or a repetition of negative age codes?In contemporary media and scientific contexts, it has become increasingly popular to launch today’s elderly as different from previous generations of older people, especially emphasized is that today’s elderly will have more attitude and set higher demands on society. The TV-series Pensionärsjävlar is based on this idea of today’s and tomorrow’s elderly as different and more rebellious than previous generations. The purpose of this article is to analyze and discuss how age and age codes are used as a prerequisite for, but also are challenged in the series. The result shows that chronological age is almost absent in the series, instead age coding is performed by physical attributes and verbal acts. Most common attributes are those connected to decreased functionality, such as walker, wheelchair, walking stick etcetera. The most common taboo joked about is sexuality, and other common themes are decreased functionality,child/youth- like behavior and traffic. In the article I discuss how these themes and attributes are negotiated in relation to age.
Keywords: age; age coding; pensioner; youth